Coir fabric development and evaluation of fabric handfeel - Contreras, Aldea Mae N.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines, 2018)
The Philippine fiber and garment industry has been on the decline since the 1990s due to the phase-out of the Multi-Fiber Agreement and export demand for locally produced textiles decreased (Ong, 2012). Conversely, the local coconut industry is booming and the Philippines produces around 15 billion coconuts and exports coconut oil and desiccated coconut (Forbes, 2013). Coir is a fiber that can be extracted from coconut husks, which is a by-product of the coconut industry, and utilizing coir fiber in textiles could potentially reinvigorate the local textile industry. Coir is a tough and coarse fiber, which limits its applications, especially in apparel. This experimental research aimed to soften coir fiber, develop a fabric from the resulting fibers and explore its potential textile applications. The coir fiber was procured from a local gardening supplies shop and softened by soaking and heating in an alkaline solution (40 % Na2S, 10 % NaOH and 6 % Na2CO3) for 2 hours. The treated fibers were blended with cotton at a 70:30 ratio and spun into yarn, resulting to a 70:30 cotton-coir yarn. The resulting yarn was used as the weft and woven with pure cotton yarns as the warp. Selected BS Clothing Technology students who have studied textiles and textile properties evaluated the handfeel of the resulting fabric. The results of the evaluation showed that the cotton-coir fabric had a very rough and scratchy surface due to the protrusions of coir fiber, which greatly limits its potential textile applications. It was also evaluated as a stiff and crisp fabric. The fabric was recommended for use in home furnishing and décors. For apparel use, the surface quality needed to be improved, but it had desirable aesthetic appeal. It could be used as a decorative detail in apparel, as long as it did not touch the skin. The researcher recommends using an alternative method of softening the coir to improve the fabric handfeel and expand the potential applications of softened
Thesis (B.S. Clothing Technology) -- University of the Philippines Diliman
Keywords: Coir industry -- Philippines; Textile fabrics -- Philippines; Clothing trade -- Philippines